Rancang Bangun Pembangkit Listrik Piko Hidro (PLTPH) Menggunakan Turbin Archimedes Screw Sebagai Penerangan Tenda Darurat - Bintang Fellix Romansyach Nindjau; Reza Rahmadian; Mahendra Widyartono; Ayusta Lukita Wardani (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The need for electrical energy in modern life is crucial; however, conventional energy sources such as coal, gas, oil, and nuclear have limitations in their availability. Therefore, people are searching for renewable alternatives for electrical energy. This study aims to evaluate the voltage, current, and revolutions per minute generated by a DC generator, as well as the efficiency of a turbine intended for emergency lighting in a tent. The research involves testing the turbine at seven different head heights, ranging from 20cm to 80cm. In this experiment, a water pump with a flow rate of 5 liters per second is used to supply power to three 8-watt DC lamps. The research results indicate that the maximum power that can be generated for tent lighting is approximately 20.83 watts, with an efficiency of 61.09%, achieved at a head turbine height of 50cm.